(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the contradictions between local customs and current legislation in Uzbekistan. Traditional social practices - in particular, on issues such as the age of marriage, dowry, marriage between relatives, inheritance distribution, and the role of women in society - sometimes create situations that contradict formal legal norms. Therefore, there is a need to raise legal awareness and culture in society, and to harmonize traditional values with legal reforms. The article puts forward an analytical approach to the social roots of these conflicts, their legal consequences, and possible solutions.